2017
DOI: 10.18203/2320-1770.ijrcog20172948
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study to assess the maternal and paternal fetal attachment among the expectant mothers and fathers

Abstract: Background: Bonding during pregnancy refers to a process through which a pregnant women experiences feelings and emotions for her fetus, interacts with her fetus and develops a maternal identity during pregnancy. The mothers and fathers interact differently with the developing fetus, but evidences for these differences are contradictory. It is important to recognize the factors influencing maternal fetal attachment and paternal fetal attachment because of the effects on future health and development of the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 5 publications
4
5
3
Order By: Relevance
“…This finding was supported in the study of Ustunsoz et al 15 The study of Kaur and Mamta, Sagar also found a statistically significant relationship between parity and MFA and PFA scores. 22 This result, which is consistent with the literature, may be explained with the references to high levels of excitement and demand among the nulliparous women and their partners so that they may be more likely to develop prenatal attachment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This finding was supported in the study of Ustunsoz et al 15 The study of Kaur and Mamta, Sagar also found a statistically significant relationship between parity and MFA and PFA scores. 22 This result, which is consistent with the literature, may be explained with the references to high levels of excitement and demand among the nulliparous women and their partners so that they may be more likely to develop prenatal attachment.…”
Section: Discussionsupporting
confidence: 89%
“…The only study in the literature on the relationship between length of marriage and MFA and PFA scores did not find a significant relationship between these variables. 22 Although this study did not find a statistically significant relationship between length of marriage and MFA scores, PFA scores were found to be negatively associated with length of marriage. We believe that this finding may be related with the possibility that the interest of expectant fathers on marriage and pregnancy may decrease over time.…”
Section: Discussioncontrasting
confidence: 71%
“…On the other hand, this same result disagrees with the findings of Kaur & Mamta (2017). They had conducted a comparative study to assess the maternal and paternal fetal attachment among the expectant mothers and fathers in Iran (15) . Their results showed that 90% of their female expectant mothers had strong maternal fetal attachment level.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as lack of social support, an unplanned pregnancy, marital problems, are all linked with lower MFA. 39 Thus, it could be said that the presence of any of these factors during pregnancy adversely affects both MFA and stress.…”
Section: Discussionmentioning
confidence: 99%